The incidence of brain metastases among patients with metastatic breast cancer: a systematic review and meta-analysis. Issue 6 (23rd December 2020) - Kuksis, Markus; Gao, Yizhuo; Tran, William; Hoey, Christianne; Kiss, Alex; Komorowski, Adam S; Dhaliwal, Aman J; Sahgal, Arjun; Das, Sunit; Chan, Kelvin K; Jerzak, Katarzyna J
Abstract: Background: Patients with metastatic breast cancer (MBC) are living longer, but the development of brain metastases often limits their survival. We conducted a systematic review and meta-analysis to determine the incidence of brain metastases in this patient population. Methods: Articles published from January 2000 to January 2020 were compiled from four databases using search terms related to breast cancer, brain metastasis, and incidence. The overall and per patient-year incidence of brain metastases were extracted from studies including patients with human epidermal growth factor receptor-2 positive (HER2+), triple negative, and hormone receptor (HR)+/hormone receptor negative (HER2−) MBC; pooled overall estimates for incidence were calculated using random effects models. Results: 937 articles were compiled, and 25 were included in the meta-analysis. Incidence of brain metastases in patients with HER2+ MBC, triple negative MBC, and HR+/HER2− MBC was reported in 17, 6, and 4 studies, respectively. The pooled cumulative incidence of brain metastases was 31% for the HER2+ subgroup (median follow-up: 30.7 months, IQR: 24.0–34.0), 32% for the triple negative subgroup (median follow-up: 32.8 months, IQR: 18.5–40.6), and 15% among patients with HR+/HER2− MBC (median follow-up: 33.0 months, IQR: 31.9–36.2). The corresponding incidences per patient-year were 0.13 (95% CI: 0.10–0.16) for the HER2+ subgroup, 0.13 (95%CI: 0.09–0.20) for the triple negative subgroup, and only 0.05 (95%CI: 0.03–0.08) for patients with HR+/HER2− MBC. Conclusion: There is a high incidence of brain metastases among patients with HER2+ and triple negative MBC. The utility of a brain metastases screening program warrants investigation in these populations.